Kedudukan Bezitter Terhadap Objek Warisan - Ruff, Elis; Tjoanda, Merry; Uktolseja, Novyta (PATTIMURA Law Study Review, 2024)
Inheritance law is part of marriage law. This relationship occurs because inheritance law regulates how a person's property and wealth will be distributed to the heirs. The inheritance process will refer to the transfer of property from heirs to heirs. The law authorizes the heirs to own the right to inheritance. Inheritance that has no heirs will be under the control of the heritage hall, in the Indonesian Civil Code Material rights, namely, Bezit, Eigendom, and material rights over other people's property, will be exercised by Bezitter after that, where Bezitter who has good faith has the right to acquire ownership of the object. The possession of an inheritance by a Bezitter can occur if the heirs do not exist or are unable to perform their rights and obligations. This refers to the application of the principle of expiration, to study and discuss the right of bezitter to the object of inheritance and to discuss the legal consequences of the object of inheritance that is leased to other parties. The legal research method used in examining this problem is normative juridical, which is based on primary, secondary, and tertiary legal materials, and uses a statute approach and a conceptual approach. The result of this writing explains that Bezitter's position on the control of an inheritance according to Article 1185 can be done if, a Bezitter who has in good faith has managed and cared for an inheritance for a long period of time (verjaring) is allowed to control an inheritance if the heirs are unable to exercise their rights and obligations. Legal protection can be done by implementing relevant laws and regulations as a preventive step in maintaining security and law enforcement.